Assessment of drinking water quality at the tap using fluorescence spectroscopy. (15th November 2017) - Heibati, Masoumeh; Stedmon, Colin A.; Stenroth, Karolina; Rauch, Sebastien; Toljander, Jonas; Säve-Söderbergh, Melle; Murphy, Kathleen R.
Abstract: Treated drinking water may become contaminated while travelling in the distribution system on the way to consumers. Elevated dissolved organic matter (DOM) at the tap relative to the water leaving the treatment plant is a potential indicator of contamination, and can be measured sensitively, inexpensively and potentially on-line via fluorescence and absorbance spectroscopy. Detecting elevated DOM requires potential contamination events to be distinguished from natural fluctuations in the system, but how much natural variation to expect in a stable distribution system is unknown. In this study, relationships between DOM optical properties, microbial indicator organisms and trace elements were investigated for households connected to a biologically-stable drinking water distribution system. Across the network, humic-like fluorescence intensities showed limited variation (RSD = 3.5–4.4%), with half of measured variation explained by interactions with copper. After accounting for quenching by copper, fluorescence provided a very stable background signal (RSD < 2.2%) against which a ∼2% infiltration of soil water would be detectable. Smaller infiltrations would be detectable in the case of contamination by sewage with a strong tryptophan-like fluorescence signal. These findings indicate that DOM fluorescence is a sensitive indicator of water quality changes in drinking water networks, as long as potential interferents are taken into account. Graphical abstract: Highlights: A biologically-stable drinking water network exhibited stable chemical properties. Copper leached from pipes quenched visible wavelength fluorescence. Fluorescence would be sensitive tracer of entrained soil water or sewage.